IoT and Edge Computing for Architects : Implementing edge and IoT systems from sensors to clouds with communication systems, analytics, and security, 2nd Edition /: Implementing edge and IoT systems from sensors to clouds with communication systems, analytics, and security, 2nd Edition. (2020) - Lea, Perry
No abstract available